The Effects of Direct-fed Microbial, Primalac®, or Salinomycin Supplementation on Intestinal Lactate Isomers and Cecal Volatile Fatty Acid Concentrations in Broilers1 - Croom, J.; Chichlowski, M.; Froetschel, M.; McBride, B.W.; Qui, R.; Koci, M.D. (International Journal of Poultry Science, 2009)
Direct-Fed Microbials (DFM) are a putative alternative to the feeding of sub-therapeutic levels of antibiotics in the production of poultry and other livestock species. This study was designed to examine the effects of a commercial DFM (Primalac®), or salinomycin (SAL), a commonly used antibiotic and coccidiostat supplement, on fermentation patterns and lactate production in the cecum and the lower intestinal tract of broiler chickens. L-lactate and total lactate concentrations in the digesta fluid of the ileum decreased (P